Does Foreign Interest Rate Determine Islamic Stock Prices? - Machtra, Catona; Majid, Muhammad Shabri Abdul; Dawood, Taufiq Carnegie (Univeristas Islam Bandung, 2023)
This paper aims to investigate whether foreign interest rate determines Islamic stock prices vis-à-vis domestic interest rate. The method applied is the Autoregressive Distributed Lag (ARDL) model to Indonesian data from January 2008 to June 2018. The study found a long-run negative relationship between foreign interest rate with both Islamic and conventional stock prices. Additionally, foreign interest rate is more important than domestic interest rate in determining the price of both types of stocks. Although Islamic stocks are affected by foreign interest rate dynamics, they are less responsive to changes of the Libor than conventional equities. In addition, it is found that GDP, money supply and real exchange rate has a long-run positive relation with both stock price. Thus, although Islamic equity prices are not insulated against foreign interest rates, they are less responsive to international financial markets movements than conventional stocks. For policy, authorities should pay close attention to foreign interest rate dynamics. While policy makers and fund managers in a dual capital market can use Islamic stocks to provide cushion against dynamics of international funds market.